A model of holistic support to the schools implementing change and evaluation of distributed leadership effects - Rupnik Vec, Tanja (Vodenje v vzgoji in izobraževanju, 2014)
This paper describes an innovative approach to change implementation into school communities developed by The National Education Institute (NEI) in Slovenia from 2003 to 2006. The model of holistic support focuses on supporting organizational learning and improvement of practice through distributed leadership. With the help of leadership team plan the principals provide direction and monitor the work teachers do with their students. The authors conducted a study (semi-interviews) on what strategies of distributed leadership are used by principals to support the change process, and how members of school teams experience some aspects of team dynamics (survey). The results show that with this approach principals can influence school climate and enhance the quality of teachers% work with students. Quality of communication and cooperation in the leadership teams were good due to systematic teambuilding activities, which were focused on group dynamics.
Keywords: change process; distributed leadership; holistic model; kakovost; leadership; ravnatelji; šolska klima; teams; vodenje